Регуляризацiя iндукованих середовищем переходiв у наноскопiчних системах - Teslenko, V. I.; Petrov, E. G. (Publishing house "Academperiodika", 2019)
A novel method for regularization of environment-induced relaxation transitions in nanoscopic systems is proposed. The method, being compatible with the chaotic, stochastic, and transient time scales, is physically consistent and mathematically strict. It allows one to correctly reduce the evolution of a system to a master equation for the balance of populations of its states with the probabilities of transitions between states well satisfying both the temperature-independent activationless limit and the Arrhenius exponentially temperature-dependent activation-like limit. The results obtained are applied to the description of the kinetics of temperature-independent desensitization and degradation observed in receptor and circadian protein macromolecules.